Model Dye-Sensitized Solar Cell dan Aplikasinya Berdasarkan Data Temperatur Harian: Studi Kasus Pangkalpinang - Noor, Aliefia; Hamdini, Meri; Ramadina, Salsabila; Tiandho, Yuant (UNIVERISTAS PGRI MADIUN, 2020)
Dye-Sensitized Solar Cells (DSSC) is photovoltaic with a dye that functions as an acceptor of sunlight. The great potential of using DSSC lies in the ease of the synthesis process, and the dyes used can come from plants. However, like most other solar cells, increasing the operating temperature can degrade the DSSC performance and thus decrease the efficiency. This article presents a model of the relationship between the effect of temperature on DSSC performance. The model proposed is derived from the DSSC equivalence with a diode circuit. By confirming the experimental research results, it is known that the model presented in this study has excellent accuracy on various DSSC performance parameters (R2> 0.99). The performance studied includes the I-V curve's shape, the value of the short-circuit current, the diode leakage current, and the open-circuit voltage. Based on daily temperature data in Pangkalpinang City, the potential performance of the DSSC could also be determined when it was developed in Kep. Bangka Belitung. The short-circuit current value obtained is in the range of 14 A with a voltage of 0.6 V. It is hoped that this proposed model can be information for the development of DSSC because of its enormous potential application in Indonesia.